PREVALENCE OF ANAEMIA AMONG RURAL PRE-SCHOOL CHILDREN OF MAHARASHTRA, INDIA - Arlappa, N; Balakrishna, N; Laxmaiah, A; Brahmam, GNV (Indian Journal of Community Health, 2012)
Background: Anaemia continues to be a severe public health nutritional problem in India affecting all physiological groups, even after the National Nutritional Anaemia Prophylaxis Programme has been in operation for more than three decades. Objective: To assess the prevalence of anaemia among rural pre-school (1-5-years) children of Maharashtra. Methods: A community based cross-sectional study was carried by National Nutrition Monitoring Bureau (NNMB) covering a total of 404 (Boys-243; Girls-161) pre-school children. Information of socio-demographic particulars was obtained and the finger prick blood samples were collected for the estimation of haemoglobin levels by cyanmethmoglobin method. Results: The result shows that 59.2 % (CI: 54.4-64.0) of the rural pre-school children of Maharashtra were anaemic, and the prevalence was significantly (p<0.001) higher (76.5% with CI: 68.1-84.9) among 1-3-year children as compared to 53.6% in 4-5-year- children. Stepwise Logistic regression analysis also revealed that the risk of anaemia in 1-3-year-age group was three times higher (OR= 2.8; 95% CI: 1.6-4.7). Conclusion: Anaemia was severe public health nutritional problem (>40%) among rural pre-school children of Maharashtra. Therefore, appropriate intervention measures such as supplementary iron & folic acid, periodic deworming and health & nutrition education should be strengthened. The community needs to be encouraged to diversify their diets by consuming iron rich foods.